Youth Empowerment to Grow Creative Business Interest - Mohammad Djaelani; Arif Rachman Putra (Journal of Social Science Studies (JOS3), 2021)
The era of globalization has hit almost all areas of human life around the world. Progress and change occur in tandem with the swift currents of globalization. The development of a very fast era like today requires human resources to have high quality to achieve a more prosperous life. Youth has extra potential compared to other community groups. The existence of youth is very necessary in the midst of society for community empowerment efforts, especially youth. However, the success of youth in youth empowerment efforts has not been explored optimally and more deeply, so that it makes the attraction itself to dig deeper into youth empowerment to cultivate creative business interests. This study uses a descriptive qualitative research approach because this research presents, describes or describes descriptive data about youth empowerment to foster creative business interest. the results obtained by the youth have an interest in doing creative business. however, this was hindered by the existing training and capital. for some people, the training that has been done so far has had an impact on their desire to open a business compared to applying for jobs elsewhere.